Development of Android Based Try Out Application For National Exam Of Vocational Theory In Vocational School Accompanied With Learning Outcomes Recommendation - Apriyanto, Muklis Eko; Yuana, Rosihan Ari; Indriayu, Mintasih (Universitas Sebelas Maret, 2019)
This research aims to develop the Android based for National Exam Tryout of Vocational Theory of SMK TKJ. Thisapplication also gives recommendation according the tryout result. This research also aims to know the feasibility ofthis application based on an assessment by media expert and student of TKJ department. this research use researchand development method (R & D) which adapted from Waterfall software development model. Waterfall methodincludes 5 stages: (1) requirement definition; (2) system and software design; (3) implementation and unit testing; (4)integration and unit testing; (5) operation and maintenance. The assessment results from media experts amounted to4.37 for Android-based front-end applications and for 4.42 for web-based back-end applications, user-rating back-endapps got a value of 4.65, while ratings from students were 4.53. Based on the feasibility study It can be concluded thatthe Android applications can be used. This application has advantages that are: 1) the application can display therecommendation of exam results; 2) the application displays questions randomly; 3) app can run on old Androidversion.